Otimização matemática: cálculo dos extremos de uma função - Nunes, Evandro Barbosa (2014)
Optimization problems seek to maximize or minimize a certain function, they play an important role in the real world. Many practical applications of sciences like engineering and economics can be formulated through optimization problems, for example, minimizing the amount of energy used in a factory or maximizing the investment of a person. In this work we will deal with issues of functions of one, two or three variables in the search for the point whose value is maximum or minimum, will be treated contents that can be worked in high school, as the Inequality of Means, Quadratic Function and also themes that can be explored in graduate course, in the case of Derivative and Method of Lagrange, all threads have interesting examples of applications of the concepts studied.